2017
DOI: 10.1111/psyp.12825
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the roles of orienting and inhibition in the Concealed Information Test

Abstract: The Concealed Information Test (CIT) is a well-validated tool for physiological and behavioral detection of concealed knowledge. Two distinct theoretical frameworks have been proposed to explain the differential responses to the concealed critical items: orienting response theory versus arousal inhibition theory. klein Selle, Verschuere, Kindt, Meijer, and Ben-Shakhar (2016), however, argued for a response fractionation model and showed that, while the skin conductance reflects pure orienting, both the respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 77 publications
7
53
1
1
Order By: Relevance
“…Two kinds of items were presented: critical probe items, such as a murder weapon related to an incident under investigation, and noncritical irrelevant items unrelated to the incident but in the same category as the critical items, such as other weapons. This CIT method measured the skin conductance response as a sign of autonomic nervous system (ANS) arousal probably related to the orienting reflex (klein Selle, Verschuere, Kindt, Meijer, & Ben‐Shakhar, ). Although the ANS‐based CIT was reasonably accurate (90% sensitivity, 100% specificity), the ANS may have been only indirectly responsive to specific stimuli, whereas the P300 might have provided a more accurate index of recognition.…”
Section: Early Studies Of the P300 Citmentioning
confidence: 99%
“…Two kinds of items were presented: critical probe items, such as a murder weapon related to an incident under investigation, and noncritical irrelevant items unrelated to the incident but in the same category as the critical items, such as other weapons. This CIT method measured the skin conductance response as a sign of autonomic nervous system (ANS) arousal probably related to the orienting reflex (klein Selle, Verschuere, Kindt, Meijer, & Ben‐Shakhar, ). Although the ANS‐based CIT was reasonably accurate (90% sensitivity, 100% specificity), the ANS may have been only indirectly responsive to specific stimuli, whereas the P300 might have provided a more accurate index of recognition.…”
Section: Early Studies Of the P300 Citmentioning
confidence: 99%
“…This was intended to induce response inhibition in the noncooperative participants. However, it may also have created response inhibition in cooperative participants, because the instructions-be cooperative yet still press NO for the familiar faces-were contradictory (klein Selle et al, 2015(klein Selle et al, , 2017.…”
Section: Witness Cooperationmentioning
confidence: 99%
“…However, it is unclear whether the P300 component in the CIT reflects the orienting response or inhibition (Donchin, Heffley, Hillyard, Loveless, Maltzman, Öhman, Rosler, Ruchkin, & Siddle, 1984). Several previous studies suggested that the CIT effect on the P300 was caused by OR, without inhibition (Matsuda, Nittono, & Ogawa, 2013;Rosenfeld, Ozsan, & Ward, 2017) in line with the electrodermal measuresused by Klein Selle et al (2016Selle et al ( , 2017. However, another study reported no CIT effect without inhibition (Kubo & Nittono, 2009) in accord with the heart rate and respiration measures of Klein Selle et al (2016Selle et al ( , 2017.…”
Section: Introductionmentioning
confidence: 57%
“…Several previous studies suggested that the CIT effect on the P300 was caused by OR, without inhibition (Matsuda, Nittono, & Ogawa, 2013;Rosenfeld, Ozsan, & Ward, 2017) in line with the electrodermal measuresused by Klein Selle et al (2016Selle et al ( , 2017. However, another study reported no CIT effect without inhibition (Kubo & Nittono, 2009) in accord with the heart rate and respiration measures of Klein Selle et al (2016Selle et al ( , 2017. Because inhibition is defined as an executive function that enables an individual to deliberately and intentionally inhibit a dominant, automatic, prepotent response (Miyake, Frie-A.…”
Section: Introductionmentioning
confidence: 57%